An evaluation of an InPouch TV culture method for diagnosing Trichomonas vaginalis infection. - Borchardt, K A (1991)
A new culture method for Trichomonas vaginalis, the InPouch TV test, was evaluated for its sensitivity and specificity in supporting growth of trichomonads. Five clinical isolates remained viable for periods from 41 to 131 days. A strain from the ATTC 30001 remained viable for 91 days. As few as four trichomonads/ml of culture medium could be viewed microscopically within 24 h. Doubling time for growth of trichomonad varied between 5 to 8 h. In a clinical study of 102 wet-mount negative specimens, 15 culture positive patients were observed with the InPouch TV test compared with 12 of the same patients with Hollander's fluid medium.